Effect of layer number on bending behavior of 3D spacer composite plates produced with different methods - Erdem, Serkan; Kaman, Mete Onur; Gür, Mustafa (Fırat University, 2022)
In this study, the three-point bending behavior of laminated composite plates reinforced with three-dimensional (3D) spacer fabric was experimentally investigated. Composite plate production was carried out using hand lay-up and vacuum infusion (VARI) method. Three-point bending test results of composite plates produced as a single layer were experimentally compared. Afterwards, composite plates with 2 and 3 layers were obtained by vacuum infusion method and load displacement graphs were obtained by subjecting them to three-point bending test. There was no significant difference between the load carrying capacities of the single-layer composite plates produced by hand lay-up and vacuum infusion method in the three-point bending test. According to the three-point bending test, the maximum load obtained 105 N in hand lay-up production is 8% greater than the vacuum infusion method. While the maximum load was 602 N in the plate produced in the 2-layer vacuum infusion method, it was obtained as 923 N in the 3-layer.
Keywords: Mechanical Engineering; Makine Mühendisliği